HucMSC Conditioned Medium Ameliorate Lipopolysaccharide-Induced Acute Lung Injury by Suppressing Oxidative Stress and Inflammation via Nrf2/NF-κB Signaling Pathway. (14th August 2021) - Tang, Yue; Ding, Fengxia; Wu, Chun; Liu, Bo
Abstract : Acute lung injury (ALI) is a common clinical syndrome in the cardiac intensive care unit with a high mortality rate. Inflammation and oxidative stress have been reported to play a crucial role in the development of ALI. Previous studies have shown that human umbilical cord mesenchymal stem cells (hucMSCs) have anti-inflammatory and antioxidative effects in various diseases. However, the anti-inflammatory and antioxidative effects of the hucMSC conditioned medium (CM) on LPS-induced ALI remain unclear. Therefore, in this study, we assessed whether the hucMSC conditioned medium could attenuate LPS-induced ALI and the underlying mechanisms. Mice were randomly divided into four groups: the control group, PBS group, LPS+PBS group, and LPS+CM group. The lung histopathology and bronchoalveolar lavage fluid (BALF) were analyzed after intervention. The Nrf2/NF- κ B signaling pathway and its downstream target genes were tested, and the cytokines and growth factors in CM were also measured. The results showed that CM significantly attenuated the histological alterations; decreased the wet/dry weight ratio; reduced the levels of MPO, MDA and ROS; increased SOD and GSH activity; and downregulated the level of proinflammatory cytokines such as IL-1 β, IL-6, and TNF- α . Furthermore, CM promoted the expression of Nrf2 and its target genes NQ01, HO-1, and GCLC and inhibited the expression of NF- κ B and its target genes IL-6, IL-1 β, and TNF- α . These effects may be closely related to the large amounts of cytokines and growth factors in the CM. In conclusion, our results demonstrated that CM could attenuate LPS-induced ALI, probably due to inhibition of inflammation and oxidative stress via the Nrf2/NF- κ B signaling pathway.